Synthesis of C-prenylated analogues of stilbenoid methyl ethers and their cyclic dihydrobenzopyranyl derivatives as potential anti-inflammatory agents - Pizova, Hana; Malanik, Milan; Smejkal, Karel; Oravec, Michal; Bobal, Pavel (RSC advances, 2022)
An efficient and versatile synthesis of the naturally occurring C-prenylated stilbenoid methyl ethers and their synthetic analogues is presented. The synthesis represents a six step convergent process including an optimised C-prenylation method. Furthermore, during the demethylation process, six new dihydro-benzopyranyl derivatives were obtained and isolated.